2019
DOI: 10.1002/ece3.5763
|View full text |Cite
|
Sign up to set email alerts
|

Sex matters: Otolith shape and genomic variation in deacon rockfish (Sebastes diaconus)

Abstract: Little is known about intraspecific variation within the deacon rockfish (Sebastes diaconus), a recently described species found in the northeast Pacific Ocean. We investigated population structure among fish sampled from two nearshore reefs (Siletz Reef and Seal Rock) and one offshore site (Stonewall Bank) within a <50‐km2 area off the Oregon coast. Fish from the three sample sites exhibited small but statistically significant differences based on genetic variation at >15,000 neutral loci, whether analyzed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 130 publications
(231 reference statements)
2
25
1
Order By: Relevance
“…These results stand in contrast to previous studies, that have reported tens to hundreds of significantly differentiated variants with mean autosomal male-female F ST values ranging from 1% to 45% [14][15][16][17][18][19] . These studies suggest strong, pervasive sexually antagonistic viability selection acting across the genomes of various species, which would be puzzling in light of theoretical observations and simulations indicating that strong allelic divergence between the sexes requires high sex-specific mortality rates to overcome the homogenizing effect of meiotic segregation occurring every generation 13 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results stand in contrast to previous studies, that have reported tens to hundreds of significantly differentiated variants with mean autosomal male-female F ST values ranging from 1% to 45% [14][15][16][17][18][19] . These studies suggest strong, pervasive sexually antagonistic viability selection acting across the genomes of various species, which would be puzzling in light of theoretical observations and simulations indicating that strong allelic divergence between the sexes requires high sex-specific mortality rates to overcome the homogenizing effect of meiotic segregation occurring every generation 13 .…”
Section: Discussioncontrasting
confidence: 99%
“…Recent research has looked for these effects by identifying alleles with high male-female F ST 10,12,13 , a normalized measure of allele frequency difference. Such studies across a range of taxa have suggested that potentially hundreds of autosomal loci are subject to ongoing sexually antagonistic selection with many differentiated loci having male-female divergence values of at least 10% [14][15][16][17][18] , and some reaching even as high as 45% 19 . The production and maintenance of such large male-female differences would require strong, ongoing selection, because alleles are homogenized every generation by meiotic segregation 12,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2019; Vaux et al. 2019) or from breeding individuals (Dutoit et al. 2018), yet it remains unclear how much information about SA selection is contained within these estimates.…”
Section: Indirect Approaches For Identifying Sa Genesmentioning
confidence: 99%
“…As the sample available for each species was small (and the body sizes of specimens varied within and among groups), no conclusions could be drawn with regard to within‐species variability of the otoliths such as sexual dimorphism (Teimori et al ., 2020; Vaux et al ., 2019), ontogenetic variation (Vignon, 2012; Więcaszek et al ., 2020) or asymmetry between right and left otoliths (Lord et al ., 2012; Lychakov et al ., 2008; Panfili et al ., 2005). Nonetheless, some preliminary remarks can be made based on the comparison between otolith groups.…”
Section: Figurementioning
confidence: 99%